Evaluation of an endoscopic suturing device for transoral outlet reduction in patients with weight regain following Roux-en-Y gastric bypass - Jirapinyo, P.; Slattery, J.; Ryan, M. B.; Dayyeh, B. K. Abu; Lautz, D. B.; Thompson, C. C. (Endoscopy, 2013)
Background and study aims: A dilated gastrojejunal anastomosis (GJA) is thought to be associated with weight regain in patients with Roux-en-Y gastric bypass (RYGB). Due to a high rate of perioperative morbidity, surgical revision is not generally performed. The aim of this study was to assess the technical feasibility, safety, and early outcomes of a procedure using a commercially available endoscopic suturing device to reduce the diameter of the GJA.Patients and methods: This was a retrospective analysis of 25 consecutive patients who underwent transoral outlet reduction (TORe) for dilated GJA and weight regain. An endoscopic suturing device was used to place sutures at the margin of the GJA in order to reduce its aperture. On chart review, clinical data were available at 3, 6, and 12 months. Results: Patients had regained a mean of 24 kg from their weight loss nadir and had a mean body mass index of 43 kg/m2 at the time of endoscopic revision. Average anastomosis diameter was 26.4 mm. Technical success was achieved in all patients (100 %) with a mean reduction in anastomosis diameter to 6 mm (range 3 – 10 mm), representing a 77.3 % reduction. The mean weight loss in successful cases was 11.5 kg, 11.7 kg, and 10.8 kg at 3, 6, and 12 months, respectively. There were no major complications. Conclusion: This case series demonstrated the technical feasibility, safety, and efficacy of performing gastrojejunostomy reduction using a commercially available endoscopic suturing device. This technique may represent an effective and minimally invasive option for the management of weight regain in patients with RYGB.